Challenging the Idea of Europe: Representations of Female Transnational Experiences in Chérissa Iradukunda's Broken Object - Castillo Soto, Maria Auxiliadora (Satura, 2024)
Chérissa Iradukunda published her first book - Broken Object - in 2023, sharing her transnational story of resettlement from her home country of Burundi to the Netherlands. The story is presented through the life experiences of Mylene, the main character. Mylene is a teenage girl who goes through a so-long awaited journey with her father to reunite with the rest of her family. Unbeknownst to her, the resettlement process turns out to be very complex, and changes in her family dynamics complicate it even further. Considering these difficulties, the story portrays how an absence of a feeling of ‘homeness’ in the protagonist(s) results in a lack of safety and belonging to her new surroundings. The present analysis considers Broken Object as an alternative discourse to the traditional idea of Europe as superior and universal. Through the representations of 1) the broken and 2) the gazed female subjects, this intersectional analysis brings forth alternative transnational experiences, especially those written by Black women authors, for new modes of identity construction. The paper encompasses a close reading method with a thematic deductive analytic approach, following Olaf Zenker’s dimensions of identity. Although Iradukunda does not speak for a whole group or represent the majority, her unique story adds significant value as an alternative proposal of representations and experiences to those used to forge the idea of Europe.